Water Splitting on Multifaceted SrTiO3 Nanocrystals: Computational Study - Sokolov, Maksim; Mastrikov, Yuri A.; Zvejnieks, Guntars; Bocharov, Dmitry; Kotomin, Eugene A.; Krasnenko, Veera (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Recent experimental findings suggest that strontium titanate SrTiO3 (STO) photocatalytic activity for water splitting could be improved by creating multifaceted nanoparticles. To understand the underlying mechanisms and energetics, the model for faceted nanoparticles was created. The multifaceted nanoparticles’ surface is considered by us as a combination of flat and “stepped” facets. Ab initio calculations of the adsorption of water and oxygen evolution reaction (OER) intermediates were performed. Our findings suggest that the “slope” part of the step showed a natural similarity to the flat surface, whereas the “ridge” part exhibited significantly different adsorption configurations. On the “slope” region, both molecular and dissociative adsorption modes were possible, whereas on the “ridge”, only dissociative adsorption was observed. Water adsorption energies on the “ridge” (−1.50 eV) were significantly higher than on the “slope” (−0.76 eV molecular; −0.83 eV dissociative) or flat surface (−0.79 eV molecular; −1.09 eV dissociative). © 2021 by the authors. Licensee MDPI, Basel, Switzerland. Published under the CC BY 4.0 license.
The financial support of M-ERA.NET2 Sun2Chem project is greatly acknowledged by E.K. Authors thank Dr. Marjeta Ma?ek Kr?manc and prof. Chi-Sheng Wu, for the fruitful discussions. The financial support of FLAG-ERA JTC project To2Dox is acknowledged by Y.A.M. This paper is based upon the work from COST Action 18234, supported by COST (European Cooperation in Science and Technology). The support is greatly acknowledged by Y.A.M. and V.K. The grant No. 1.1.1.2/VIAA/l/16/147 (1.1.1.2/16/I/001) under the activity of Post-doctoral research aid is greatly acknowledged by M.S. and D.B. The Institute of Solid State Physics, University of Latvia (Latvia) as the Centre of Excellence has received funding from the European Union?s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-Teaming Phase2 under grant agreement No. 739508, project CAMART2 . The computer resources were provided by the Stuttgart Supercomputing Center (project DEFTD 12939) and Latvian Super Cluster (LASC).
Keywords: Research Subject Categories::NATURAL SCIENCES; DFT; OER; Stepped surface; STO; Water splitting